Bilateral Fractures of the Frmoral Neck - Sakinaga, Yasuo; Yonei, Toru; Ninomiya, Takumi (Orthopedics & Traumatology, 1994)
Eighteen bilateral fractures of the upper end of the femur were analysed retrospectively. The incidence of bilateral fracture was 11.0% of the total. A preponderace of female patients was found in the bilateral fracture group. However no difference in sex was found between the unilateral and bilateral groups. There was a higher percentage of symmetrical fractures in the bilateral group.